Rumores (2021)
Rumores is a virtual sexual education course born from the idioms identified in day-to-day life of a group of colombian teens. Created from human-centered design, an update to a traditional course created by the company Tirando X Colombia, was proposed in a way that its contents could be presented as an answer to the real wants and needs of its direct users. It¿s expected that with this intervention in the discourses about sexuality and sex that traverse these teenagers, and building linguistical bridges with them, the effectiveness of the work that the company does in preventing teenage pregnancies increases.